(untitled) (International Journal of Environmental Sciences, 2025)
This work considers the intricate associations among Greenwashing, perceived CSR, consumer trust in a brand and consumer behavior, using Environmental Concern as a moderating factor. The effect of both greenwashing and genuine CSR on company reputation was examined by testing a moderated mediation model using Structural Equation Modeling in SmartPLS. Structured Likert-scale questionnaires were used to collect information and all constructs were confirmed to be both reliable and valid (AVE > 0.50 and HTMT < 0.90). Results show that brand trust decreases and consumer behavior changes negatively due to greenwashing, but increases with perceived CSR. Trust in a brand has an essential role as an intermediate factor in both processes. Consumer reactions to ethical or deceitful brand behaviors are further exaggerated by Environmental Concern. When consumers are very concerned about the environment, they pay more attention to CSR and greenwashing. The results of the analysis are then translated into useful strategies by using a Multi-Objective Optimization (MOO) method with a simulated Pareto-based model. The results indicate that equity trust and desired consumer responses can be achieved if firms hold their CSR intensity at 0.95 or above and their greenwashing level at 0.12 or below. With the help of 3D graphics, brand managers spot key decision areas for the organization.